Assessing the Interaction Effects of Institutional Quality and Energy Mix on Carbon Emissions: A Panel Data Analysis of Emerging Economies - Hafiz Muhammad Saad; Wajid Alim*; Iqra Shakeel (`, 2025)
This paper examines the causes of environmental sustainability and carbon dioxide (CO) emissions due to integrating structural, economic, and governance issues among a sample of multiple countries over the period of 2015 to 2024. Through robust econometric models, such as stationarity tests, Granger causality, and panel generalized method of moments (GMM), the study measures the dynamic interdependencies between clean energy adoption (CE), carbon-intensive energy (EC), economic growth (EG), trade openness (TO), and urbanization (U). Findings indicate that renewable energy is the best positive influence on sustainability, whereas fossil energy use, which has been linked to emissions in the past, also shows a balanced case of role management with efficiency and regulatory advances. Sustainability is reinforced by economic growth and trade openness due to the positive effect on promoting technological adoption and global integration, and urbanization has a modest effect that is, nevertheless, statistically insignificant in its nature of transition. The results of Granger causality establish bidirectional relationships between sustainability, growth, and trade and place emphasis on mutually reinforcing relations, whereas the one-way relation of ES on fossil energy consumption and urbanization draws attention to the proactive aspect of the sustainability policies in determining the long-term structural transition. All the findings together support the idea that governance, modernization of technology, and balanced structural change are the means to align development with climate ambitions. This empirical study has helped policymakers in need to foster sustainable growth towards the global climate agenda. Keywords: Carbon Emission, Clean Energy Adaptation, Carbon-intensive Energy, GMM